The Uniqueness of Sayau Kapa Momorun Dance in Dusun Tindal Ethnic Kota Belud Sabah - Nurul Aisyah Othman; Humin Jusilin; Salbiah Kindoyop; Noria ak Tugang (2018)
The Dusun Tindal ethnic group derives its name from the words ‘Dusun’ which refers to race or origin and ‘Tindal’ meaning land or hills. The Dusun Tindal is often associated with a refined ability to produce high- quality handicraft items such as the traditional kuron pottery. Kuron is an integral part of the Sayau Kapa Momorun, a well- known traditional dance performance in Kampung Malangkap Kapa, Kota Belud. The dance is unique due to its significance in the production of kuron. The Dusun Tindal community has turned the process of kuron- making into a traditional dance complete with its own set of movements, music and costumes. This study is an exploration of the uniqueness of the Sayau Kapa Momorun as a dance representation of the traditional kuron pottery of the Dusun Tindal in Kota Belud. The research utilises the fieldwork methods of observation, interview and audio visual recording.